2022
DOI: 10.32743/unitech.2022.98.5.13674
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Operating Features of Forestry and Wood Processing Equipment Under the Climatic Conditions of the Far North

Abstract: Выходные данные статьи и справка о публикации: в день оплаты статьи Рассылка печатных журналов и оттисков: 05.09.2022

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The analysis of scientific works of modern domestic and foreign researchers [1][2][3][4] has shown that the production of wood fiber semi-finished products is one of the most effective directions in the field of wood waste processing. It is established that the main consumers of wood fiber semi-finished products are the board and pulp and paper industries, the demand for finished products of which has a constant tendency to increase.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of scientific works of modern domestic and foreign researchers [1][2][3][4] has shown that the production of wood fiber semi-finished products is one of the most effective directions in the field of wood waste processing. It is established that the main consumers of wood fiber semi-finished products are the board and pulp and paper industries, the demand for finished products of which has a constant tendency to increase.…”
Section: Introductionmentioning
confidence: 99%